The Analysis of Teacher Efforts to Developing Students Interpersonal and Intrapersonal Intelligence in Learning Activities - Bredyna Agnesiana; Susanto Susanto; Devin Mahendika; Sumarni Rumfot; Ellyzabeth Sukmawati (Departement of Mathematics Education, 2023)
Identifying the teacher's initiatives to foster students' interpersonal and intrapersonal intelligence during the learning process was the aim of this study. This study was done in a high school and used a qualitative approach to gather descriptive information from people's written or spoken words and observable behavior. Data gathered via observation, interviewing subjects, and documenting events. The results of the study show that teachers make learning plans in the form of syllabi and lesson plans, and that they use the right methods, approaches, and media when teaching to foster students' development of their interpersonal and intrapersonal intelligences. The techniques, approaches, and media employed are extremely effective and can aid in students' growth of their interpersonal and intrapersonal intelligence in learning.